Cervical cancer prevention in Burkina Faso: a stakeholder’s collaboration for the development of awareness messaging - Ouedraogo, Samiratou; Bamogo, Assanatou; Tiendrebeogo, Georges; Kaboré, Simon; Turcotte-Tremblay, Anne-Marie; Maiga, Mamoudou; Kagoné, Samdapawindé Thérèse; Lompo, Olga Mélanie; Meda, Nicolas (Frontiers in Oncology, 2024)
Background Cervical Cancer stands as the second leading cause of both incident female cancers and deaths in Burkina Faso. Unfortunately, the prevention, the early detection and care of cervical cancers are suboptimal at individual, institutional, and national levels. In October 2023, we organised a stakeholder’s workshop to develop cervical cancer awareness messaging for the disease control in the country. Methods A one-week workshop was organised with stakeholders working toward improving health in general or women health and wellbeing. A participatory, learning, and adaptive approach were used to facilitate discussions and activities, ensuring the contribution of all participants. Contextual evidence-based and empirical elements about cervical cancer burden and preventive strategies were presented to the participants by key informants. These served as the foundation for a collaborative formulation of messaging contents that aimed at raising awareness about cervical cancer. Results Sixty-two participants from 28 organizations attended the workshop. They work mainly at local and international non-governmental organizations, civil society organizations, universities, university hospitals and research centers, ministry of health. During the first and second days of the workshop, the participants explored cervical cancer data, its preventive and treatment options available in Burkina Faso, communication strategies for behavioral change and determinants of the use of prevention and health promotion services. During the following three days, 3 working groups were formed to define strategies, and key messages adapted to diverse tools and targeted audiences. All information were validated during plenary sessions before the end of the workshop and available to all participants and their organizations for cancer awareness activities. Conclusion Upon conclusion of the workshop the participants provided insightful information for the development of cervical awareness messaging in Burkina Faso. They formed the first community of practice to serve as a dynamic platform for implementation, monitoring, evaluation and continued learning activities.